Modeling of switching mechanism in GeSbTe chalcogenide superlattices - Yu, Xiaoming (Sci Rep, 2015)
We study the switching process in chalcogenide superlattice (CSL) phase-change memory materials by describing the motion of an atomic layer between the low and high resistance states. Two models have been proposed by different groups based on high-resolution electron microscope images. Model 1 proposes a transition from Ferro to Inverted Petrov state. Model 2 proposes a switch between Petrov and Inverted Petrov states. For each case, we note that the main transition is actually a vertical displacement of a Ge layer through a Te layer, followed by a lateral motion of GeTe sublayer to the final, low energy structure. Through calculating energy barriers, the rate-determining step is the displacive transition.